FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN DIRI PADA WANITA INFERTILITAS - Nurhasyanah Nurhasyanah (Journal of Research and Measurement in Psychology, 2017)
Abstract This study aims to determine the factors that influence self-acceptance in women who experience infertility. This study uses a qualitative method approach to the case study technique. Characteristics among the study subjects had been married for at least three years, had never given birth, and there is no any proximity to the researchers. The data was collected using the methods of observation and interviews. Data were analyzed using qualitative data analysis with a technical examination of the validity of the data using the technique of triangulation. Triangulation is used in this study is the triangulation of data sources and methods. Triangulation of data sources that extract data from research subjects and significant others. Triangulation method to get the data by observation, interviews, and documentation. The study found that the two subjects in this study is able to accept yourself, but picture yourself acceptance in both different and influenced by different factors as well. At first the subject there are several internal factors that influence the acceptance of the subject, including an understanding of self, realistic expectations, the influence of success, the identification of the person who has a good adjustment, self-concept is stable. External factors that influence the acceptance of him as there are no obstacles in the environment, positive social attitudes, and parenting little future. On the subject of the second, it can be seen several internal factors that influence the acceptance of himself that is, an understanding of themselves, have realistic expectations, did not experience severe emotional disturbance, identification with a person who has a good adjustment, a broad perspective of self, and self-concept subjects stable. In addition, there are also external factors that affect selfacceptance on the subject that the two of them, good parenting in childhood, positive social attitudes, and there are no obstacles in the environment. The third external factor is equal to the external factors that affect self-acceptance on the subject first. Keywords: Self-Acceptance, Women, Infertility